NONCONVULSIVE SEIZURES AND NONCONVULSIVE EPILEPTIC STATUS. NEW THERAPEUTIC OPPORTUNITIES - A. V. Lebedeva; V. E. Khomutov; . .; D. V. Guz (Эпилепсия и пароксизмальные состояния)
Nonconvulsive epileptic seizures make the most part of all attacks which are registered in patients with mostly a focal epilepsy, the status of nonconvulsive seizures (NCSE) represents the most difficultdiagnostics problem for neurologist, epileptologist or reanimatologist. However, the given problem is insufficiently studied till now, not numerous data on diagnostics and treatment of NCSE are presented in literature.According to literature more than 30 % of patients of emergency care departments with infringement of consciousness of unknown reason are patients with NCSE.»New» antiepileptic drugs for intravenous introduction (valproates, levetiracetam,lacosamid) may give us new opportunitiesand perspectives in treatment of patients with serial nonconvulsive seizuresand NCSE.